2009
DOI: 10.1007/s10344-009-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of scat identification in distribution surveys: American mink, Neovison vison, in the northern highlands of Scotland

Abstract: Distribution data for elusive species are often based on detection of field signs rather than of the animal itself. However, identifying field signs can be problematic. We present here the results of a survey for American mink, Neovison vison, in the northern highlands of Scotland to demonstrate the importance of verifying field sign identification. Three experienced surveyors located scats, which they identified as mink scats, at seven of 147 sites surveyed and "possible" mink scats at a further 50 sites. Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 29 publications
4
66
0
2
Order By: Relevance
“…The use of scats to carry out this type of ecological study dealing with carnivores has been questioned due to possible misidentification of the specific scat origin (e.g., Davison et al 2002;Janecka et al 2008;Harrington et al 2010). Even so, a number of studies, also based on genetic analyses of scats, showed a high accuracy of the involved surveyors (Zuercher et al 2003;Prugh and Ritland 2005;Barja et al 2007;Harrington et al 2008;Rosellini et al 2008;.…”
Section: Wildcat Scat Surveysmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of scats to carry out this type of ecological study dealing with carnivores has been questioned due to possible misidentification of the specific scat origin (e.g., Davison et al 2002;Janecka et al 2008;Harrington et al 2010). Even so, a number of studies, also based on genetic analyses of scats, showed a high accuracy of the involved surveyors (Zuercher et al 2003;Prugh and Ritland 2005;Barja et al 2007;Harrington et al 2008;Rosellini et al 2008;.…”
Section: Wildcat Scat Surveysmentioning
confidence: 99%
“…Thus, according to IUCN quantitative criterion A.2.b, it would be possible to qualify the species as critically endangered, endangered, vulnerable, or near threatened depending on observed reductions of 80%, 50%, 30%, or 20%, respectively, in the proposed AI within a period of 10 years or three generations (IUCN 2001). Only in those areas of Europe with the presence of the other wild felid species, Iberian lynx (Lynx pardinus, Temminck 1827) or European lynx (Lynx lynx, Schreber 1777), could confusion with wildcat scats be possible and genetic analysis of scats would be necessary (Guzmán et al 2004;Alda et al 2008;Harrington et al 2010). Even so, the technical staff and scientists working on recovery programs of Iberian lynx in Spain are convinced that most scats can be differentiated without genetic analyses when field experience is extensive enough (as the size, shape, and color of lynx scats considerably differ; Gil-Sánchez (personal communication)).…”
Section: Scat Surveys For Monitoring Wildcat Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scat is therefore used frequently in wildlife ecology to evaluate the presence/absence of elusive animals (Palomares et al 2002), estimate animal abundances (Hurlbert 1971, Kohn et al 1999, Prugh et al 2008, characterize diets (Reynolds and Aebischer 1991, Symondson 2002, Deagle et al 2005, and investigate animal health or disease ecology (Gompper et al 2003, Liccioli et al 2012. Historically, scats have been identified to species by morphology, but the morphological distinctions among scats produced by mammalian mesopredators can be difficult to discern and improperly identified specimens can confound and even invalidate research (Harrington et al 2009). Despite some successes with field based scat identifications (Zuercher et al 2003, Prugh andRitland 2005), which are more reliable when made in conjunction with additional natural sign (e.g.…”
mentioning
confidence: 99%